Review of the leafhopper genus Kalasha Distant (Hemiptera: Cicadellidae: Hylicinae) - Tang, Jiu; Zhang, Yalin (Zootaxa, 2019)
The Oriental leafhopper genus Kalasha Distant is reviewed with redescriptions and photos of all known species, and two new species are described and illustrated. The female ovipositor of K. nativa Distant is described and photographed. Kalasha sondaica Jacobi, 1914 is proposed as a junior synonym of K. nativa Distant, 1908. A key to species of the genus is provided. Kalasha nativa Distant, originally described from India (Assam), is recorded from Malaysia, Thailand and Viet Nam for the first time, also representing the first records of the genus from Malaysia and Thailand.